Genome‐wide association study on Alzheimer's disease CSF profiles in the EMIF‐AD MBD and ADNI datasets. (20th December 2022) - Neumann, Alexander; Ohlei, Olena; Dobricic, Valerija; Vos, Stephanie J. B.; Zetterberg, Henrik; Visser, Pieter Jelle; Tijms, Betty; Sleegers, Kristel; Bertram, Lars; ,
Abstract: Background: Genome‐wide association studies (GWAS) of Alzheimer's disease (AD) have identified several risk loci, but many remain unknown and disease mechanisms are often unclear. Using CSF biomarkers of AD as outcome may aid in gene discovery and in elucidating disease processes. We previously demonstrated that six CSF biomarkers (β‐amyloid, total/phosphorylated tau, NFL, YKL‐40, and neurogranin) can be robustly clustered into five profiles by principal components (PC) analysis, each representing statistically independent biological processes. Our goals here were: 1. To identify common genetic variants associated with these profiles; 2 To assess the role of associated variants in AD pathophysiology and 3. Explore potential sex differences. Method: We performed GWAS analyses for each of the five biomarker PCs in two multi‐center studies, i.e.: the EMIF‐AD and ADNI. In total, 931 participants with no, mild cognitive impairment or AD had sufficient genetic and biomarkers information. Overall, we tested the effect of 7, 433, 949 common SNPs (MAF>1%; incl. X chromosome) and 19, 511 protein‐coding genes. Genome‐wide significant variants were followed up with structural equation models to test whether any of the biomarker PCs mediate the effect of the variants on diagnostic status. We further tested sex interactions with a moderated mediation model. Result: Five loci showed genome‐wide significant association with the PCA‐based CSF profiles, three of which were previously described ( APOE, TMEM160B and CHI3L ), and two were novel (rs145791381 and GRIN2D ). Mediation tests indicated that variants in the APOE region affect AD status via two statistically independent processes: amyloid and tau pathology, but not via neuronal injury/inflammation. Vice versa, TMEM106B, CHI3L, and rs145791381 affected AD only via neuronal injury/inflammation. GRIN2D was associated with synaptic functioning, but was unrelated to AD risk. PCA‐based CSF profiles did not differ between sexes, neither did associations between CSF profiles and diagnosis status. Interestingly, however, genetic effects were stronger in females for most pathways. Conclusion: The results suggest for the first time an involvement of an intergenic region on chromosome 9p21.3 (rs145791381) in AD‐related disease processes, as well as a role of the glutamate receptor GRIN2D in synaptic functioning. Furthermore, the study highlights the importance of sex differences in the genetics of AD.